<u>Comment</u>
If I don't know what was before the comma in M(, –1) I can't solve this
Answer:
b i believe the answer is
Answer:
see explanation
Step-by-step explanation:
If A +B = 45° then tan(A+B) = tan45° = 1
Expanding (1 + tanA)(1 + tanB)
= 1 + tanA + tanB + tanAtanB → (1)
Using the Addition formula for tan(A + B)
tan(A+B) =
= 1 ← from above
Hence
tanA + tanB = 1 - tanAtanB ( add tanAtanB to both sides )
tanA + tanB + tanAtanB = 1 ( add 1 to both sides )
1 + tanA + tanB + tanAtanB = 2
Then from (1)
(1 + tanA)(1 + tanB) = 2 ⇒ proven
Answer:
the answer is 2
Step-by-step explanation:
2/3/1/3 were going to take 1/3 multiply it by 2/3 and switch the nume and the deno.
2/3 x 3/1 = 6/3
6/3 = 2